2018
DOI: 10.1080/10286020.2017.1421177
|View full text |Cite
|
Sign up to set email alerts
|

Three new diphenyl ether derivatives from the fermentation products of an endophytic fungus Phomopsis fukushii

Abstract: Three new diphenyl ethers (1-3), together with four known isopentylated diphenyl ethers derivatives (4-7), were isolated from the fermentation products of an endophytic fungus Phomopsis fukushii. Their structures were elucidated by spectroscopic methods, including extensive 1D and 2D NMR techniques. Compounds 1-3 were evaluated for their anti-methicillin-resistant Staphylococcus aureus (anti-MRSA) activity. The results revealed that compounds 1 and 2 showed strong inhibitions with inhibition zone diameters (IZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…yunna-nensis. Compounds 11-13, exhibited potent anti-MRSA activity, with 20.2, 17.9 and 15.2 mm inhibition zones, respectively, when tested at 50 µg concentration in 6 mm discs [23].…”
Section: Diaporthe (Asexual State: Phomopsis)mentioning
confidence: 99%
See 1 more Smart Citation
“…yunna-nensis. Compounds 11-13, exhibited potent anti-MRSA activity, with 20.2, 17.9 and 15.2 mm inhibition zones, respectively, when tested at 50 µg concentration in 6 mm discs [23].…”
Section: Diaporthe (Asexual State: Phomopsis)mentioning
confidence: 99%
“…The fungus Diporthe vochysiae LGMF1583 isolated from Vochysia divergens yielded two new carboxamides, vochysiamides A (23), and B (24, Figure 2). Compound 24 inhibited Klebsiella pneumoniae carbapenemase-producing (KPC), MSSA, and MRSA with MIC of 0.08, 1.0, and 1.0 µg/mL, respectively, and compound 23 was active against KPC with a MIC of 1.0 µg/mL.…”
Section: Diaporthe (Asexual State: Phomopsis)mentioning
confidence: 99%
“…Diphenyl ethers have been reported to possess significant antibacterial activity, especially against Gram-positive bacteria, and structure–activity relationship analysis showed that prenylation might play an important role to increase antibacterial activity of the compounds. The isopentenyl flavonoids displayed antibacterial activity against Gram-positive pathogens with multidrug-resistance, which may be due to compounds interacting with the phospholipids of the bacterial membrane, dissipating the proton motive force, and degrading membrane permeability .…”
Section: Resultsmentioning
confidence: 99%
“…From this ecological aspect, endophytic fungi are an important source of antibacterial substances, especially as a source of compounds active against MDR bacteria . In recent years, more and more diphenyl ether derivatives have been isolated from plant endophytic fungi and have attracted special attention due to their excellent antibacterial activity. …”
mentioning
confidence: 99%
“…Antibiotic resistance is an important issue due to the frequent use of antibiotics for the treatment of common bacterial infections. The enhancement of antimicrobial resistance is Antibiotics 2023, 12, 1201 2 of 15 strengthening the pathogenicity and virulence of infectious microbes [1][2][3]. Therefore, finding new antibiotics is crucial to combat these resistant bacteria [4].…”
Section: Introductionmentioning
confidence: 99%